Corbel strut and tie modeling – Experimental verification. (August 2020) - Abdul-Razzaq, Khattab Saleem; Dawood, Asala Asaad
Abstract: ACI 318-14 analyzes reinforced concrete corbel by shear friction (SF) and/or strut-and-tie modeling (STM). This work presents the results of experimental tests conducted on three reinforced concrete corbels that had a height of 390 mm and a width of 115 mm. The corbels had different shear span to effective depth ratios (a/d), which were 0.5, 1 and 1.5, respectively. Each test specimen was analyzed using both SF and STM to make a comparison between the experimental results. The cracking load, failure load, deflection, crack pattern, steel reinforcement strains, concrete surface average strains and locations of failure were recorded and discussed for the tested corbels. The findings revealed that, in the case of corbels with a/d = 0.5, the shear friction ultimate capacity ( P SF ) and the STM ultimate capacity ( P STM ) were less than the experimental failure load ( P f ) by about 15% and 22%, respectively. In addition, P SF a n d P STM were less than P f by about 18% and 27%, respectively, when a/d = 1. In contrast, in the case of a/d = 1.5, P SF a n d P STM were less than P f by about 32% and 37%, respectively. In conclusion, in the case of a/d < 1, both STM and SF can be used, although STM is more conservative due to its safety factors. In the case of a/d = 1–2, STM is more accurate than SF. However, if a/d exceeds 2, the corbel should be treated as a conventional cantilever beam.